Analysis of local geomagnetic index under the influence of equatorial electrojet (EEJ) at the equatorial Phuket geomagnetic station in Thailand. Issue 5 (1st September 2022) - Myint, Lin M.M.; Hozumi, Kornyanat; Saito, Susumu; Supnithi, Pornchai
Highlights: Generate local K-indices from the equatorial region for space weather monitoring. Investigate the effect of EEJ on the equatorial local K-index. Control the EEJ impact using a proper L9 value. Examine the monthly mean of the equatorial magnetic fields in high/low solar year. Examine the diurnal variations of the equatorial magnetic fields. Abstract: The local K-index is an important proxy to monitor geomagnetic disturbances due to the solar wind in space weather study. The diurnal variation of geomagnetic fields observed in the magnetic equatorial region is dominated by the equatorial electrojet (EEJ), and the variation of EEJ is directly related to the local ionospheric dynamics; therefore, in this work, the local K-index is generated by based on the geomagnetic field measurement at an equatorial geomagnetic station in Phuket, Thailand and the effects of EEJ on the computed local K-indices are analyzed. At each station, an L9 (the lower limit for K = 9) value is set to develop a conversion table between the magnetic range scales and K-indices, and that L9 value must be assigned based on the characterization of the geomagnetic variations at that station. In this work, suitable L9 values are determined by analyzing the distributions of the local K-index and the planetary geomagnetic index, Kp-index. According to the results in the present study, the L9 value of 500 nT can provide local K-indices that can classify the geomagnetic disturbances more correctly. The results show that 40% of the local K-index is consistent with the Kp-index, and about 45% of the local K indices are ±1 deviated from Kp-indices. It is found that using the suitable L9 value can partially control the EEJ's dominance on K-index. Moreover, we investigated the seasonal and day-to-day variability of the diurnal variation of the geomagnetic fields from the Phuket station. Upon reviewing the data, the equatorial geomagnetic field variations were consistent with the planetary geomagnetic activity levels, and the day-to-day changes of the daytime field amplitudes were relatively high in the high solar activity year and moderate in the low solar activity year.